Scientists and nuclear war: Liberating mankind from the threat of its own making - T. Jacob, T. Jacob (Universitas Gadjah Mada, 1986)
This article reiterated the peace warsituation during the first 40 years of the Atomic Age. The nuclear arms race poses not only an unprecedented threat to mans existence, but has taken millions of pre-detonation victims of the nuclear war, in the forms of morbidity and mortality due to famine, infectious diseases, poverty, ignorance, and peripheral wars in the Third World. The resources of out planet are diverted from welfare efforts to the unlimited production of genocidal weapons. World scientists, immediately after the atomic bombing of Hiroshima and Nagasaki, had warned mankind of the danger of a nuclear disaster, and physicians, true to their professional oath and ethics, have joined efforts to prevent nuclear war, since medicine will then be unable to cope with its innumerable, immeasurable and compound casualties, as they had done in previous war. The Third World countries, which mostly obtained their independence after World War suffered severely from the escalating arms race and could not escape the global consequences of a nuclear war anywhere, but still feel reluctant to voice their displeasure, consider it an irrelevant prob. km amidst their many-sided struggles towards progress, or are simply ignorant of the last threat that has confronted their existence and growth. It is, therefore, the duty of Third World physicians to also inform their patients about the imminent danger against their health, welfare and survival,. as they have been doing to their individual patients since the days of Hippocrates. Key Words: nuclear war - medical polemology - genocide - enthanatics - medical ethics